Reaction scope and mechanistic insights of nickel-catalyzed migratory Suzuki–Miyaura cross-coupling - Yuqiang Li (Nature Portfolio, 2020)
Migratory cross-coupling reactions are powerful tools to form bonds at predictable positions. Here the authors report a nickel-catalyzed migratory Suzuki–Miyaura cross-coupling of unactivated alkyl electrophiles with aryl and vinyl boron reagents and provide experimental and computational mechanistic evidence.